Effectivenes of a short course in improving knowledge and skill of teacher’s school health program (UKS) in nutrition assesment - Tri Siswati; Herawati Herawati (Berita Kedokteran Masyarakat (BKM), 2018)
Background: School Health Program (UKS) is agent to promote and increase health status of school children. Headmaster have  responsiblility to monitoring  school health children, including nutritional status. Objectives: to asses the effectiveness of a short course on knowledge and skills of UKS’s teachers in the assessment of children nutritional status. Methods: This was a before after  experimental quasy,  in Yogyakarta in 2015. Intervention was a short course  20 hours  designed to develop the knowledge and skill of UKS’s theacher.  Subject were 37 UKS’s teachers in Sleman Regency, with criterian complete attending. Data were analyzed by t-test using SPSS. Results: Most of the respondents were  public elementary school (68.6%), male (59.4%), 31-40 years old (34.4%), sports teachers (65,5%), managing UKS for 5 years (37.5%), never got similar short course (94.8%). There were an increase of knowledge and skills by 4.9±3.2 and 3±2.8 respectively,  statistically significant. Conclusion: The study provides evidence for effectivenes to increase  knowledge and skills UKS’s theachers in  monitoring  nutritional status of children.